Modeling of Split Ring Resonators loaded microstrip line with different orientations - Rajni Rajni; Gurwinder Singh; Anupma Marwaha (International Journal of Electrical and Computer Engineering (IJECE), 2015)
This paper presents the different circuit approaches of the electric and magnetic interaction of Single Split Ring Resonator (SRR) loaded microstrip line. We loaded the microstrip line with planar square split ring resonator in different configurations and orientations. The modeling behavior of metamaterials-based microstrip lines loaded with single and two-mirrored split ring resonators is analyzed numerically in two orientations (with gap of SRR parallel and perpendicular to the line). The full wave simulations are performed for the single and two-mirrored split ring resonators loaded microstrip inside a waveguide with ‘High Frequency Structure Simulator’ software. The equivalent circuit parameters are obtained for the single split ring resonator loaded with microstrip line with the gap parallel and near to the line from transmission line theory  that make use of just the resonance frequency and minimum of the reflection coefficient. The simulation of different orientations of split ring resonator gives better reflection coefficient and wider frequency.